S Konsep Integrasi Nilai-Nilai Keislaman Dalam Pembelajaran Pendidikan Agama Islam pada Lembaga Pendidikan - Deden Heri; Uus Ruswandi (Jurnal Dirosah Islamiyah, 2022)
In the context of the religious structure of Indonesian society, Islamic education has an important role in shaping the character and character of the nation. Islamic education has the function of actualizing Islamic values ​​in the midst of changes in people's lives which are full of shifts and clashes of current values. In fact, the implementation of Islamic religious education, which takes place at various levels of education, is still less successful in working on the attitudes and behavior of religious subjects of students and building the nation's morals and ethics. For this reason, this paper will discuss the reformulation of the pattern of integration of Islamic values ​​in Islamic education. Keywords: Integration, Islamic Values, Islamic Religious Education.